MENGGUNAKAN SHOPEE SELLER CENTRE PADA E-COMMERCE SHOPEE UNTUK MENAIKKAN PENJUALAN (TOKO : AKAIPRINT) - Rizky Trianda, Rendi (JEBS (Journal of Economic and Business Student), 2023)
E-Commerce is increasingly in demand by the public because of its convenience and broad market reach. The knowledge needed to choose E-Commerce in an online trading business. E-Commerce Shopee is the most accessed in Indonesia, making it a bigger opportunity to reach buyers. Therefore the need for Knowledge to increase sales by using the Shopee Seller Center by using the Descriptive Analysis method on the akaiprint shop object. The result is that the Shopee Seller Center is very useful for optimizing Products, Orders, and all the features in it. Having this knowledge is expected to increase sales in Shopee E-Commerce